Intelligence, Social Mobility, and Growth - Hassler, John; Mora, José V. Rodríguez (American Economic Review, 2000)
We develop a model where the allocation of human resources, intergenerational social mobility, and technological growth are jointly determined. High growth endogenously increases the equilibrium return to innate cognitive ability and makes the allocation of individuals depend more on innate ability and less on social background. Individuals with a higher level of innate cognitive ability can deal better with less known, but more productive, technologies and thus choose a higher rate of technological growth. A social allocation based on innate ability and high growth will thus reinforce each other, implying the possibility of multiple endogenous growth equilibria. (JEL J62, O1)